Comparison of 404 Patients with Right- and Left-sided Colon Cancer in Uganda: Differences in Clinicopathological Profile - Wismayer, Richard; Kiwanuka, Julius; Wabinga, Henry; Odida, Michael (Research Developments in Medicine and Medical Science Vol. 5, 2023)
Introduction: In Western countries right-sided colon cancers (RSCC) present at an older age and advanced stage. Researchers believe that there is a difference between left-sided colon cancer (LSCC) and RSCC. In Uganda however, it is unknown whether differences exist in the pathological profile between RSCC and LSCC. The aim of this study was to determine differences in clinicopathological characteristics between RSCC and LSCC in Ugandan patients. Methodology: A cross-sectional study was conducted in which colorectal adenocarcinoma formalin-fixed paraffin-embedded tissue (FFPE) blocks were obtained from 2008 to 2021. Colorectal specimens were obtained from prospectively recruited patients. In the retrospective study arm, FFPE blocks and data were obtained from the archives of pathology laboratory repositories. Parameters studied included age, sex, location of the tumour, grade, stage, lymphovascular (LVI) status and histopathological subtype between LSCC and RSCC. Results: Patients with RSCC were not older than those with LSCC (mean age, 56.3 years vs 53.5 years; p=0.170). There was no difference in the stage between RSCC and LSCC. Poorly differentiated tumours were more commonly found in RSCC than in LSCC (18.7% vs 10.1%; p=0.038). Moderately and poorly differentiated colonic tumours were more common with RSCC (89.3%) than with LSCC (75.1%) (p=0.007). Younger patients had more poorly differentiated tumours than older patients (19.6% versus 8.6%; p=0.002). LVI was more common with RSCC than with LSCC (96.8% vs 85.3%; p=0.014). Mucinous adenocarcinoma (MAC) was more common with RSCC (15.8%) compared to LSCC (8.5%) (p=0.056) although statistical significance was borderline. Conclusions: Clinicopathological features of RSCCs tend to be different from those of LSCCs. RSCCs tend to be associated with MAC, a higher grade and LVI status compared to LSCC. LSCC and RSCC present predominantly with an advanced stage; therefore, national screening programmes for the early detection of CRC are necessary to reduce mortality in our Ugandan population.